Bolstering resilience through teacher-student interaction: Lessons for school psychologists. (April 2016) - Liebenberg, Linda; Theron, Linda; Sanders, Jackie; Munford, Robyn; van Rensburg, Angelique; Rothmann, Sebastian; Ungar, Michael
Schools are often the only formal service provider for young people living in socio-economically marginalized communities, uniquely positioning school staff to support positive psychosocial outcomes of youth living in adverse contexts. Using data from 2, 387 school-going young people [Canada ( N  = 1, 068), New Zealand ( N  = 591), and South Africa ( N  = 728)] living in marginalized communities and who participated in the Pathways to Resilience study, this article reviews how student experiences of school staff and school contexts moderated contextual risks and facilitated resilience processes. Findings of these analyses affirm that school staff play an important role in moderating the relationship between resilience resources and community/family risk in both global North and global South contexts. Findings hold important implications for school psychologists, including the need to champion the ways in which teachers can scaffold resilience resources for young people through the quality of the relationships they build with students.